Pacific Philosophy Forum. - University of the Pacific. Philosophy Institute; International Institute of Philosophy ([Stockton, Calif.] Pacific Philosophical Institute, 1962)
Vol. 2 includes an issue called Special edition: International Institute of Philosophy. Tolerance, its foundations and limits in theory and practice; papers and discussions at two California conferences.
Keywords: Philosophy -- Periodicals; Political science -- Periodicals